The Great Masquerader: a successful pulmonary vein isolation with cryoablation for paroxysmal atrial fibrillation manifesting with recurrent syncopal episodes - Mohd Said, Mohd Ridzuan; Mukhtar, Murshidah Ainun; Mohd Firdaus, Mohd Al-Baqlish; Narasamuloo, Kantha Rao; Krishinan, Saravanan (Malaysia Medical Association (MMA), 2023)
Atrial fibrillation (AF) is the most common arrythmia observed in clinical practice. Early detection of AF is paramount to prevent fatal complications such as cardiomyopathy, heart failure, and stroke. Manifestation of AF varies, including being either asymptomatic or having transient palpitation, especially for paroxysmal AF. Pulmonary vein isolation (PVI) with either radiofrequency or cryoballoon ablation is the cornerstone treatment for AF, especially for those who remain symptomatic despite being on optimal treatment. Here we report a case of successful PVI with cryoablation for symptomatic paroxysmal atrial fibrillation manifesting with recurrent syncopal episodes.